2015
DOI: 10.1159/000430087
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Bilateral Irvine-Gass Syndrome following Uncomplicated Phacoemulsification, Demonstrated with Optical Coherence Tomography

Abstract: Purpose: To report a case of acute bilateral Irvine-Gass syndrome. Methods: This is an observational case report. Results: An 82-year-old man with no significant ocular history developed postsurgical pseudophakic cystoid macular edema (CME; Irvine-Gass syndrome) on consecutive phacoemulsification cataract surgeries. His initial first-eye (left) CME developed 25 days after surgery and was managed with topical preparations of dexamethasone 0.1% and ketorolac 0.4%, in addition to a routine post-cataract surgery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…However, efficacy of NSAID use on long-term visual outcomes was unclear 5,13 . Shields et al reported significant reductions in the incidence of clinical PCME with prophylactic use of topical NSAIDs, ketorolac 0,4% or nepafenac 0,1%, adjunctive to topical steroids 14 .…”
Section: Prophylactic Use Of Topical Nsaidsmentioning
confidence: 99%
“…However, efficacy of NSAID use on long-term visual outcomes was unclear 5,13 . Shields et al reported significant reductions in the incidence of clinical PCME with prophylactic use of topical NSAIDs, ketorolac 0,4% or nepafenac 0,1%, adjunctive to topical steroids 14 .…”
Section: Prophylactic Use Of Topical Nsaidsmentioning
confidence: 99%
“…CME following cataract surgery, also known as Irvine-Gass syndrome, is a well-known cause of poor vision following uneventful cataract surgery. [87][88][89] The incidence of clinical (symptomatic) pseudophakic cystoid macular edema (PCME) has been greatly reduced because of the advances in surgical techniques (approximately 0.1-2.3%) including phacoemulsification and small-incision cataract surgery. 87,90 A large Differential diagnosis of CME 7 retrospective study including 81,984 eyes revealed that the incidence of PCME in eyes without operative complications, diabetes, or risk factors was 1.17%.…”
Section: Pseudophakic and Postsurgical Macular Edemamentioning
confidence: 99%
“…Patient factors predisposing to PCME include PCME in the contralateral eye, African-American origin, and any risk factor that may disrupt the blood-retinal barrier such as diabetes mellitus, uveitis, retinal vein occlusion, retinal degeneration, macular degeneration, radiation retinopathy, epiretinal membranes, choroidal tumors, prostaglandin analog use, and aging. 87,91,92 Surgical factors include inflammation-inducing complications such as retained lens material, posterior capsule rupture, vitreous loss and vitreomacular traction, and excessive intraoperative manipulations such as mechanical pupil stretch or iris prolapse during surgery, the presence of an anterior chamber intraocular lens, filtering or other glaucoma operations, and intraocular surgeries. 87 Conventionally, PCME is classified as angiographic (seen on FA) or clinical (associated with decreased visual acuity) and acute (within 6 months) or chronic (more than 6 months).…”
Section: Pseudophakic and Postsurgical Macular Edemamentioning
confidence: 99%
See 1 more Smart Citation
“…With these process, Müller cells become swollen and lysed than eventually developed cystic changes that result in varying degree of decrease in visual acuity. This detrimental effect on visual acuity may occasionally persist and lead to permanent vision loss [3,5,[7][8][9].…”
Section: Patho-physiologic Mechanismmentioning
confidence: 99%